Isolation and characterization of a novel hydrolase-producing probiotic Bacillus licheniformis and its application in the fermentation of soybean meal - Qi, Nanshan; Zhan, Xiaoshu; Milmine, Joshua; Sahar, Maureen; Chang, Kai-Hsiang; Li, Julang (Frontiers in Nutrition, 2023)
Soybean meal (SBM) is one of the most important sources of plant-based protein in the livestock and poultry industry. However, SBM contains anti-nutritional factors (ANFs) such as glycinin, β-conglycinin, trypsin inhibitor and phytic acid that can damage the intestinal health of animals, inevitably reducing growth performance. Fermentation using microorganisms with probiotic potential is a viable strategy to reduce ANFs and enhance the nutritional value of SBM. In this study, a novel potential probiotic Bacillus licheniformis (B4) with phytase, protease, cellulase and xylanase activity was isolated from camel feces. The ability of B4 to tolerate different pH, bile salts concentrations and temperatures were tested using metabolic activity assay. It was found that B4 can survive at pH 3.0, or 1.0% bile salts for 5 hours, and displayed high proliferative activity when cultured at 50 ℃. Furthermore, B4 was capable of degrading glycinin, β-conglycinin and trypsin inhibitor which in turn resulted in significant increases of the degree of protein hydrolysis (DH) from 15.9% to 25.5% (p < 0.01) and crude protein (CP) from 44.8% to 54.3% (p < 0.001). After fermentation with B4 for 24 hours, phytic acid in SBM was reduced by 73.3% (p < 0.001), the neutral detergent fiber (NDF) and the acid detergent fiber (ADF) of the fermented SBM were significantly decreased by 38.40% (p < 0.001) and 30.20% (p < 0.05), compared to the unfermented SBM sample. Our results suggested that the effect of solid-state fermented SBM using this novel B. licheniformis (B4) strain, could significantly reduce phytic acid concentrations whilst improving the nutritional value of SBM, presenting itself as a promising alternative to phytase additives.